The Index of Multiple Deprivation 2000 and accessibility effects on health. Issue 3 (13th February 2004) - Jordan, H; Roderick, P; Martin, D
Abstract : Study objective: To investigate whether the Index of Multiple Deprivation 2000 (IMD) is more strongly related to inequalities in health in rural areas than traditional deprivation indices. To explore the contribution of the IMD domain "geographical access to services" to understanding rural health variations. Design: A geographically based cross sectional study. Setting: Nine counties in the south west region of England. Participants: All those aged below 65 who reported a limiting long term illness in the 1991 census, and all those who died during 1991–96, aged less than 65 years. Main results: The IMD is comparable with the Townsend score in its overall correlation with premature mortality ( r 2  = 0.44 v 0.53) and morbidity ( r 2  = 0.79 v 0.76). Correlation between the Townsend score and population health is weak in rural areas but the IMD maintains a strong correlation with rates of morbidity ( r 2  = 0.70). The "geographical access to services" domain of the IMD is not strongly correlated with rates of morbidity in rural areas ( r 2  = 0.04), and in urban areas displays a negative correlation ( r 2  = −0.47). Conclusions: The IMD has a strong relation with health in both rural and urban areas. This is likely to be the result of the inclusion of data in the IMD on the numbers of people claiming benefits related to ill health and disability. The domain "geographical access to services" is not associated with health in rural areas, although it displays some association in urban areas. This domain is potentially important but, as yet, inadequately specified in the IMD for the purposes of health research.